The concept of 'end of waste' and recycling of hazardous materials: in depth characterization of the product of thermal transformation of cement-asbestos. (October 2014) - Croce, A.; Allegrina, M.; Trivero, P.; Rinaudo, C.; Viani, A.; Pollastri, S.; Gualtieri, A. F.
Abstract: Selected samples of asbestos-containing material (ACM) with different Ca/Si ratios have been treated thermally at 1200°C for 15 min to obtain an 'end of waste geo-inspired material'. Before and after treatment, micro-Raman spectroscopy allowed the investigation of both powdered and massive samples by directing the laser beam onto crystals with elongated morphology, thin fibres and the matrix. In the raw samples, chrysotile and/or crocidolite were detected. After the thermal treatment, no asbestos phases were identified in the Raman spectra collected on fibrous or fibre-like morphologies. The scanning electron microscopy/energy dispersive spectroscopy investigations confirmed the onset of a pseudomorphic process during annealing, leading to the complete transformation of asbestos minerals into non-hazardous magnesium or calcium magnesium silicates such as forsterite, monticellite, a˚kermanite and merwinite. The identification of such mineral assemblages was inspired by the close inspection of a natural counterpart, the high-temperature contact metamorphic imprint due to the intrusion of a sill into carbonate rocks. The process turned out to occur largely at the solid state and involved substantial mobilization of Ca and Mg to form a spinel phase (namely MgFe2 O4 ) which was recognized in the matrix and within, or close to elongated morphologies.